Corporeality as the Hologram of Mythological Content (Based on the Prose of the Ukrainian Diaspora of the 1920s–1950s) - Slonovska, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The role and the place of the artistic truth and artistic speculation are a promising area of theoretical and practical explorations. The focus of this study is on the mythical-poetic hologram of the human body as a specific information carrier which comprises a range of important markers